KARAKTER DAN NILAI MORAL DALAM FILM SOCIAL NETWORK YANG DISUTRADARAI OLEH DAVID FINCHER - Septia Agnia; Rifari Baron (Universitas Indraprasta PGRI, 2019)
The purpose of the research is to find out 1). The main character in the film The Social Network directed by David Fincher, 2) Moral values in the film The Social Network directed by David Fincher. The method used in this research is descriptive qualitative. The technique used in this research is the literature method. The results showed: 1) The characters contained in the film